Professional, structural and organisational interventions in primary care for reducing medication errors - Khalil, Hanan; Bell, Brian; Chambers, Helen; Sheikh, Aziz; Avery, Anthony J. (Wiley, 2017)
Background: Medication-related adverse events in primary care represent an important cause of hospital admissions and mortality. Adverse events could result from people experiencing adverse drug reactions (not usually preventable) or could be due to medication errors (usually preventable).